Sequential Cr(VI) Reduction by Sodium Thiosulfate Pentahydrate Followed by CaO-Assisted Alkaline Precipitation in Settling Pond Wastewater - Muh. Agil Kurniawan; Ismail Marzuki (Candela Edutech Indonesia, 2026)
Settling pond wastewater containing hexavalent chromium, Cr(VI), requires sequential treatment that addresses oxidation state and aqueous-phase removal. Five settling ponds were screened, and SP1 and SP2 were selected as high-Cr(VI) matrices. Treatment used 0.45 µm-filtered aliquots. Cr(VI) reduction was evaluated at pH 3.0-3.3 using nominal sodium thiosulfate pentahydrate (Na₂S₂O₃·5H₂O) doses of 1-6 mg/L and contact times of 5, 15, 30, and 60 min, followed by CaO-assisted alkaline precipitation using 0.1-0.6 g CaO per 300 mL at 100, 150, and 200 rpm. Each treatment condition consisted of one process run, while Cr(VI) and total chromium were measured in analytical triplicate; responses were therefore interpreted descriptively. A 1.00 mg/L working solution prepared from a CRM certified for total chromium gave an apparent Cr(VI)-to-certified-total-Cr response ratio of 90.861% (RSD 0.373%, n = 12), which was not interpreted as Cr(VI) recovery because chromium speciation was not certified. At 5 mg/L Na₂S₂O₃·5H₂O and 30 min, Cr(VI) decreased to 0.022 mg/L in SP1 and 0.030 mg/L in SP2. Subsequent treatment with 0.6 g CaO per 300 mL produced Cr(VI) <0.004 mg/L and total chromium of 0.050 and 0.030 mg/L. Minimum combined-process Cr(VI) removals were >99.63% and >99.68%, while estimated aqueous total-chromium removals were 95.73% and 97.39%. The process is suitable for laboratory screening, but independent treatment replication, a reagent-free acidic control, unfiltered-matrix validation, species-specific Cr(VI) validation, controlled precipitation-pH experiments, and direct solid-phase characterization remain necessary before confirmatory optimization and scale-up.